2000
DOI: 10.1210/endo.141.7.7558
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Ions Positively Modulate Follicle-Stimulating Hormone- and Exogenous Cyclic 3′,5′-Adenosine Monophosphate-Driven Transcription of the P450scc Gene in Porcine Granulosa Cells*

Abstract: Given the evident modulation of FSH-induced steroidogenesis by Ca2+ in granulosa cells, we here test the hypothesis that Ca2+ controls expression of the enzymatically rate-limiting cytochrome P450(scc) (CYP11A) gene. To test this postulate, we quantitated the ability of Ca2+ to regulate: 1) transcriptional activity of a transiently transfected luciferase reporter gene driven by a 2.32-kb 5'-upstream fragment of the porcine P450(scc) gene promoter region; and 2) accumulation of endogenous P450(scc) transcripts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Earlier studies showed that progesterone synthesis in granulosa cells of several species was reduced in Ca 2ϩ -deficient incubation media (6,22,61,63), and a recent study demonstrated that the abundance of messenger RNA of cytochrome P450scc (the enzyme that catalyzes the metabolism of cholesterol to pregnenolone) in porcine granulosa cells was reduced in Ca 2ϩ -deficient medium (37). Therefore, one of the mechanisms by which Ca 2ϩ modulates steroid hormone synthesis is the increase in the transactivation of the cytochrome P450scc gene (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies showed that progesterone synthesis in granulosa cells of several species was reduced in Ca 2ϩ -deficient incubation media (6,22,61,63), and a recent study demonstrated that the abundance of messenger RNA of cytochrome P450scc (the enzyme that catalyzes the metabolism of cholesterol to pregnenolone) in porcine granulosa cells was reduced in Ca 2ϩ -deficient medium (37). Therefore, one of the mechanisms by which Ca 2ϩ modulates steroid hormone synthesis is the increase in the transactivation of the cytochrome P450scc gene (37).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that progesterone synthesis in granulosa cells of several species was reduced in Ca 2ϩ -deficient incubation media (6,22,61,63), and a recent study demonstrated that the abundance of messenger RNA of cytochrome P450scc (the enzyme that catalyzes the metabolism of cholesterol to pregnenolone) in porcine granulosa cells was reduced in Ca 2ϩ -deficient medium (37). Therefore, one of the mechanisms by which Ca 2ϩ modulates steroid hormone synthesis is the increase in the transactivation of the cytochrome P450scc gene (37). Because, in granulosa cells, the suppression of uptake of extracellular Ca 2ϩ resulted in the attenuation of progesterone production (6,22,61,63) and transcription of the cytochrome P450scc gene, and because basal lamina suppressed inward Ca 2ϩ current in differentiated granulosa cells (in the present study), it would be expected that basal lamina would decrease progesterone production in differentiated chicken granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the first scenario, cAMP appears to increase intracellular calcium by promoting calcium mobilization from intracellular stores, an effect that could be mediated by cAMP stimulation of phospholipase-Ce, whereas in the second, different G proteins (e.g., G aq/11 protein) or the b/c heterodimer of G as might be involved [41]. Further, in some models, cAMP-independent Ca 2+ influx requires the presence of extracellular calcium [59,61]. In this vein, it has been recently shown that FSH-promoted Ca 2+ influx in rat Sertoli cells is mediated by a distinct G ah /PLC-d1 pathway and that this effect is dependent on intracellular PLC-d1-mediated generation of inositol 1,4,5 triphosphate (IP3) but independent of intracellular Ca 2+ release [44].…”
Section: Follicle-stimulating Hormone and Follicle-stimulating Hormonmentioning
confidence: 99%
“…In this vein, it has been recently shown that FSH-promoted Ca 2+ influx in rat Sertoli cells is mediated by a distinct G ah /PLC-d1 pathway and that this effect is dependent on intracellular PLC-d1-mediated generation of inositol 1,4,5 triphosphate (IP3) but independent of intracellular Ca 2+ release [44]. Whatever the mechanism(s) involved in FSH-dependent Ca 2+ influx, Ca 2+ -mediated signaling seems to be important for functional differentiation of granulosa cells as suggested by recent data showing that intracellular Ca 2+ positively modulates FSH-driven transactivation of the cytochrome P450 SCC gene (cyp11A) in porcine granulosa cells [61], that Ca 2+ /calmodulindependent protein kinase IV (CaMK IV) is involved in basal cyp11A gene expression in cultured granulosa-lutein cells [62], and that fertility is markedly reduced in CaMK IV-deficient female mice [63].…”
Section: Follicle-stimulating Hormone and Follicle-stimulating Hormonmentioning
confidence: 99%
“…Based on its high content in sialic acid and acidic amino acids, a marked calcium‐binding capacity of the OPN molecule has been predicted and it indeed has been shown to bind approximately 50 atoms of calcium per molecule (Chen et al 1992) and may act as a chelator of extracellular Ca 2+ and thereby influence calcium homeostasis within the ovary. A tightly controlled calcium flux between the extra‐ and intracellular space is critical for nearly all aspects of normal ovarian function, especially for processes like steroidogenesis, follicular atresia and luteolysis (Jayes et al 2000; Makrigiannakis et al 2000; Niswender et al 2000).…”
Section: Discussionmentioning
confidence: 99%